2022
DOI: 10.1055/s-0042-1742763
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between Vestibular Disorders and Sleep Disturbance

Abstract: Introduction Vestibular pathologies cause physical and psychological symptoms, as well as cognitive problems. Objective To evaluate the deterioration in sleep quality associated with vestibular pathologies. Methods The Dizziness Handicap Inventory (DHI), the Beck Depression Inventory (BDI), the Pittsburgh Sleep Quality Index (PSQI), and the Limits of Stability test (LOS) were applied to the participants. Results We included 25 patients with Meniere's disease (MD), 22 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Furthermore, we demonstrate a national prevalence of BPPV (1.8%) similar to that of breast cancer (1.7%) (39) and liver disease (1.7%) (38). Our data further support those known relationships between having vestibular disorders and comorbid anxiety (40,41), depressive/mood (41), sleep disorders (42), concussion (43), headaches and migraines, hypertension (6), weight issues (7), heart disease (8), and stroke (9).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we demonstrate a national prevalence of BPPV (1.8%) similar to that of breast cancer (1.7%) (39) and liver disease (1.7%) (38). Our data further support those known relationships between having vestibular disorders and comorbid anxiety (40,41), depressive/mood (41), sleep disorders (42), concussion (43), headaches and migraines, hypertension (6), weight issues (7), heart disease (8), and stroke (9).…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, research undertaken by Molnár A et al 18 revealed that approximately 42.3% of individuals with dizziness displayed symptoms indicative of depression, a manifestation that exerted a notable impact on their overall quality of life. Likewise, the investigation conducted by Mutlu B et al 19 underscored elevated scores on the Beck Depression Inventory and PSQI among patients with peripheral vestibular vertigo in comparison to a healthy control group, indicating that these individuals frequently experience varying degrees of psychological stress and a diminished quality of sleep.…”
Section: Discussionmentioning
confidence: 93%